Produção de adubo orgânico a partir do lodo de esgoto cultivado com Pennisetum purpureum e Urochloa brizantha, na presença e ausência de aeração e compostado - Paulo Henrique Silveira Cardoso (2018)
Composting is one of the main processes of stabilization of sewage sludge, in which occurs the mineralization of organic matter and increase of nutrient availability. Already the phytoremediation is a process in which occurs the extraction, stabilization and/or immobilization of heavy metals and toxic organic compounds by plants. These techniques, isolated or in combination, aim to obtain a safer organic compound to be used in agriculture. In view of the above, the objective of this work was to evaluate the physical, chemical and microbial attributes and HPA content in composted sewage sludge after cultivation with Pennisetum purpureum or Urochloa brizantha in the presence and absence of aeration. The experiment was conducted in an ICA/UFMG experimental area, in DBC, with four replications and a 2x2+2 factorial scheme. The factors consisted of cultivation of P. purpureum or U. brizantha (planting density of 50 plants/m³) in sewage sludge, with intermittent aeration (30 min on/off) for 60 days (flow rate of 0.14 m³ min-1 m-3) or without aeration. The additional treatments were without cultivation with or without aeration. After 90 days of cultivation, the grass was cut, crushed and incorporated into the sewage sludge. During 60 days, the material was revolved biweekly and irrigated as needed. After this period, the material was collected and taken to the laboratory, where physical, chemical, microbial and HPA analysis were performed. The obtained data were submitted to analysis of variance with unfolding of the treatments in orthogonal contrasts at 5% of probability by the test F. The attributes granulometry, apparent and particle density, porosity, electrical conductivity and water retention capacity presented values that adequate the sewage sludge produced as substrate for seedling production. In relation to the chemical attributes, there was an increase of the CTC, CTC/C ratio, N availability and total P and Ca contents, with reduction of C/N ratio and total K and Mg contents when compared to the initial sewage sludge sample. The total Zn, Cu, Pb and Ni contents were below the maximum limit established by the CONAMA resolution nº 375. The microbial activity, evaluated by basal and accumulated respiration, the C of the microbial biomass and the metabolic and microbial quotients showed that the organic compounds produced presented stable. Among the 16 PAHs suggested by resolution proposed by the United States Environmental Protection Agency (USEPA) for monitoring, only six were quantified in the sewage sludge, of which its sum presented an average content of 1.15 mg kg-1 at the end of the experiment , being this value approximately five times lower than the maximum limit allowed by the legislation. It can be concluded that the sewage sludge compound produced can be used more safely in agricultural areas, reducing the risk of contamination of the environment.